Hedging against Over-dependence on US Security: Thailand and Philippines - Suorsa, Olli (2017)
Thailand and the Philippines are seen distancing from the US and leaning toward China. This should not be understood as switching allegiances but as refusing to choose sides and diversifying their economic, diplomatic and military relations with multiple regional powers.